Integration of AI and PBL to improve the quality of Islamic religious education: Bibliometric analysis - Rochmah Tri Hayuningsih; Dartim Dartim (Himpunan Pengembang Kurikulum Indonesia, 2025)
The development of digital technology has driven a significant transformation on the world of education, including in Islamic Religious Education (PAI) learning. This study aims to analyze the integration of artificial intelligence (AI) and the Problem-Based Learning (PBL) model to improve the quality of Islamic Education learning in the digital era. The research method used is a bibliometric study of various national and international scientific publications published in the range of 2020-2025. The results of the analysis show that the application of AI and PBL will be increasingly researched and implemented in 2024, especially related to the innovation of learning methods, the effectiveness of the learning process, and the improvement of digital-based religious literacy. The integration of AI with PBL is considered capable of strengthening students' collaboration, creativity, and problem-solving skills in the context of Islamic learning. The results of systematic analysis also identified several effective implementation models, such as AI-PBL-based hybrid classrooms and the use of chatbots or digital tutor applications in supporting collaborative learning. This research has comprehensively analyzed the integration of AI and PBL learning models in an effort to improve the quality of Islamic education in the digital era. Abstrak Perkembangan teknologi digital telah mendorong transformasi besar dalam dunia pendidikan, termasuk dalam pembelajaran Pendidikan Agama Islam (PAI). Penelitian ini bertujuan untuk menganalisis integrasi kecerdasan buatan (AI) dan model Problem Based Learning (PBL) dalam upaya meningkatkan mutu pembelajaran PAI di era digital. Metode penelitian yang digunakan adalah kajian bibliometrik terhadap berbagai publikasi ilmiah nasional dan internasional yang terbit pada rentang tahun 2020–2025. Hasil analisis menunjukkan bahwa penerapan AI dan PBL semakin banyak diteliti dan diimplementasikan pada tahun 2024, terutama terkait inovasi metode pembelajaran, efektivitas proses belajar, dan peningkatan literasi keagamaan berbasis digital. Integrasi AI dengan PBL dinilai mampu memperkuat kolaborasi, kreativitas, serta kemampuan pemecahan masalah peserta didik dalam konteks pembelajaran agama Islam. Hasil analisis sistematis pun mengidentifikasi beberapa model implementasi yang efektif, seperti hybrid classroom berbasis AI-PBL dan pemanfaatan chatbot atau aplikasi tutor digital dalam mendukung pembelajaran kolaboratif. Penelitian ini secara komprehensif telah menganalisis integrasi AI dan model pembelajaran PBL dalam upaya meningkatkan kualitas PAI di era digital. Kata Kunci: bibliometrik; kecerdasan buatan; pembelajaran berbasis masalah; pendidikan agama Islam